Cholecystomegaly: A Case Report and Review of the Literature - Mohammad Bagher Jahantab; Vahid Salehi; Saadat Mehrabi; Lotfolah Abedini; Mohammad Javad Yavari Barhaghtalab (Case Reports in Gastrointestinal Medicine)
Chronic cholecystitis or symptomatic gallbladder is a prolonged mechanical or functional disorder of abnormal gallbladder emptying. Most of the patients have recurrent pain attacks (acute biliary colic), but when pain lasts more than 24 hours, it requires urgent surgical intervention (acute cholecystitis). The length of a fully distended gallbladder is about 7 to 10 cm. We report a case of a huge and severely inflamed gallbladder, as we have just found only a few previous case reports of the huge gallbladder in the literature. This case report and review may help to find a mechanism for the development of a giant gallbladder. The patient was a 36-year-old woman, who had been known to have a symptomatic gallstone for at least three years. The patient underwent laparotomy, and a giant 22 cm roundish severely inflamed and overdistended gallbladder with wall thickening and tight adhesion to adjacent organs was found under the right liver lobe. Femininity and diabetes seem to be risk factors for developing a huge gallbladder, and several hypotheses are encountered: (1) a long-lasting obstructed cystic duct or biliary tree, and accumulation of mucosal secretion from the gallbladder epithelium, (2) an obstructed hepatic/cystic duct junction with a stone acting like a check valve and bile trapping mechanism, and (3) gallbladder dysfunction and cholecystoparesis affecting through reduced cholecystokinin and celiac parasympathetic nerve disturbance in diabetes and diabetic autonomic neuropathy. Open cholecystectomy is the technique of choice in surgical excision of a huge gallbladder; however, laparoscopy could be performed by expert hands.